1969
DOI: 10.1128/jb.99.3.824-833.1969
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Putrefactive Anaerobe 3679h During Sporulation

Abstract: Sporulation of putrefactive anaerobe 3679h was studied by observation of ultrathin sections in the electron microscope. The customary stages were observed during forespore formation, spore maturation, and liberation of the free spore. The exosporium was partially laminated and devoid of the hairlike surface projections observed on spores of some species. Atypical membrane configurations occurred in some cells, and, occasionally, cells with bipolar forespores were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…These walls have a "double track" or two-layered structure which is quite distinctive (J. V. Betz and J. G. Zeikus, Bacteriol. Proc., p. 21, 1968) and similar to that described in several other Clostridium species (12,14) and Bacillus species (11). These layers can be seen around the developing endospore in Fig.…”
Section: Sporogenessupporting
confidence: 79%
“…These walls have a "double track" or two-layered structure which is quite distinctive (J. V. Betz and J. G. Zeikus, Bacteriol. Proc., p. 21, 1968) and similar to that described in several other Clostridium species (12,14) and Bacillus species (11). These layers can be seen around the developing endospore in Fig.…”
Section: Sporogenessupporting
confidence: 79%
“…Ribi (8) but were miscalled "parasporal inclusion bodies" and were prematurely suggested to represent the same material as exosporium. Similar flakelike inclusions occur in spores of other bacilli (1, 4, 7, 9) and clostridia (15,28,29,30). The inclusions in spores of B. circulans were shown by Abram (1) to be different in negatively stained ultrastructure than the exosporial envelope.…”
Section: Discussionmentioning
confidence: 73%
“…ical. Some Clostridium strains possess this typical exosporium (15,28), but others seem to have only the laminar inner layer varying in thickness (20, 30,33). Hodgkiss, Ordal, and Cann (14) distinguished three types of exosporium in Clostridium strains.…”
Section: Discussionmentioning
confidence: 99%
“…kurstuki (Ebersold et al 1981), where up to ten laminar layers were found. Structures which are probably related have also been found in Clostridium sporogenes strain P A 3679h (Santo et a!. 1969).…”
Section: Simentioning
confidence: 67%